A Fatal Bacteremia Caused by Hypermucousviscous KPC-2 Producing Extensively Drug-Resistant K64-ST11 Klebsiella pneumoniae in Brazil - de Campos, Tatiana Amabile; Gonçalves, Laura Fernandes; Magalhães, Kelly Grace; de Paulo Martins, Vicente; Pappas Júnior, Georgios Joannis; Peirano, Gisele; Pitout, Johann D. D.; Gonçalves, Guilherme Bartolomeu; Furlan, João Pedro Rueda; Stehling, Eliana Guedes; Pitondo-Silva, André (Frontiers in Medicine, 2018)
We report a fatal bacteremia caused by Klebsiella pneumoniae in a 60-70-year-old patient from Brazil. The genomic analysis of three isolates (from blood culture, nasal and anal swabs) showed that the bacteremia was caused by a KPC-2 producing extensively drug-resistant K64-ST11 hypermucousviscous K. pneumoniae (hmKP) harboring several virulence and antimicrobial resistance genes. Although the isolates did not present virulence markers associated with hypervirulent K. pneumoniae (hvKP), they showed invasion and toxicity to epithelial Hep-2 cells; resistance to cell microbicidal mechanisms; and blood and human serum survival, evidencing their pathogenic potential. This study highlights the risk of infection caused by hmKp strains not characterized as hvKP as well as the clinical implications and difficulty of treatment, especially in elderly or immunocompromised patients.